ANALISIS KESALAHAN MATEMATIKA SISWA PADA MATERI PECAHAN KELAS IV SD NEGERI TAMANAN 3 - Yulita Ayu Pridamayanti; Trisniawati; Nelly Rhosyida (Universitas PGRI Adi Buana Surabaya, 2023)
The purpose of this research is to (1) describe the types of errors made by fourth-grade students at SDN Tamanan 3 in fraction material (2) describe what factors lead to student math errors in grade IV SDN Tamanan 3. This type of research is research descriptive quantitative. This research was conducted at class IV SD Negeri Tamanan 3, located at Tegal Rejo, Tamanmartani, Kalasan District, Sleman Regency, Yogyakarta Special Region. Data collection techniques used in this study were tests, interviews, and documentation. The results showed that (1) The results of the analysis of the questions on fractional material, fourth-grade students at SD Negeri Tamanan 3 with five questions and a total of 28 students experienced 56 cases of counting errors with a percentage of 40%, conceptual errors of 53 cases with a percentage 37.86%, systematic errors in 52 cases with a percentage of 37.14%, strategic errors in 52 cases with a percentage of 37.14%, sign errors in 43 cases with a percentage of 30.71% and translation errors in 34 cases with a percentage of 24, 29%. (2) Factors that cause students to experience errors in fractional material are a) Preconceptions or initial knowledge that is still wrong b) Low interest in learning mathematics c) Reasoning or reasoning is incomplete and d) Teaching methods are not optimal